Strategi Pengembangan Garut Packaging House (GPH) sebagai Pendukung UMKM Makanan dan Minuman: Studi Kasus Koperasi Produsen Mitra Usaha Parigel - Deddy Supriyadi; Alika Nur Fadila (J-Coop : Journal of Co-operative, 2026)
This study aims to formulate development strategies for Garut Packaging House (GPH) through business model and corporate strategy analysis. The stages include mapping the existing Business Model Canvas (BMC), conducting SWOT analysis, applying the Strategic Position and Action Evaluation (SPACE) Matrix combined with the Ansoff Matrix, and finally designing a proposed BMC. The analysis results show an IFE score of 3.07 and an EFE score of 3.15, positioning GPH in Quadrant I (Grow and Build) with recommendations for aggressive strategies. The quantitative SWOT formulation highlights market penetration and product development as priority strategies, aligned with the Ansoff framework, while market development and diversification serve as supporting strategies. The proposed BMC emphasizes expanding customer segments to MSMEs and e-commerce, developing eco-friendly packaging and creative design services, optimizing digital distribution channels, and strengthening partnerships with cooperatives, local government, and creative communities. The study recommends implementing aggressive strategies through digital promotion, service diversification, cost efficiency with lean management, and continuous monitoring to ensure competitiveness and sustainability.